Implementation of Coaching Intervention in Increasing Student Learning Motivation (Case Study of SMPN 2 Babakancikao Students) - Liza Putri Renata; Fatmawati Fatmawati; Suharyanto Soro; Nana Herdiana Abdul Rahman (Global Education Journal, 2025)
Learning motivation is one of the important factors influencing the success of students in the learning process, especially at the junior high school (SMP) level. However, in learning practice students are still found with low learning motivation, characterized by a lack of involvement, initiative, and learning responsibility. This study aims to find the implementation of coaching interventions in increasing the learning motivation of junior high school students. This research uses a case study approach with data collection methods, namely observation, interviews, and documentation studies. The data analysis technique is carried out by the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that (1) Coaching interventions are able to increase students' learning motivation through strengthening self-awareness, setting meaningful learning goals, and increasing self-regulation and student involvement in learning; (2) Coaching also strengthens the positive relationship between teachers and students so as to create a more supportive and enjoyable learning climate; (3) The implementation of coaching still experiences obstacles in the form of limited time and student readiness. This study concludes that coaching is one of the relevant pedagogical approaches and can increase the learning motivation of junior high school students if supported by a conducive school environment.